Palm Seed Germination - Alan W. Meerow (EDIS)
The purpose of this publication is to outline and discuss the various aspects of handling and germinating palm seeds in the most cost-effective and reliable manner possible. This document is BUL274, one of a series of the Environmental Horticulture Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date July 12, 1991. Reviewed and revised June 10, 2004.